Large Igneous Province thermogenic greenhouse gas flux could have initiated Paleocene-Eocene Thermal Maximum climate change - Stephen M. Jones (Nature Portfolio, 2019)
The Paleocene-Eocene Thermal Maximum constitutes one of the largest climate perturbations in Earth’s history, but its exact causes are not well known. New estimates of greenhouse gas fluxes from the North Atlantic Igneous Province at high temporal resolution show that they could have initiated this event.